Social Networking Sites: Antecedents of Social Formation and Social Presence of Millennial Generation in Digital Era - Arunprakash, A.; Srinivasan, J.; Vani, U. (International Journal of Psychosocial Rehabilitation, 2020)
In the recent scenario the trend of expressing oneself in Social networking sites is a popular phenomenon among Gen Y. An internet based tool literally used for facilitating the communication wisely, that has now used to exchange personals in several means. This socializing habit has boomed up with the existence of Face Book in the year 2004. Most recently it has developed as the world’s most preferred online networking site. It is found that there are a very few authentic studies on SNSs status in the Indian scenario especially on Gen Y. Thus it is essential to assess the determinants of Gen Y user perception among SNS. Researcher is also attempted to sort out the paperin order to get the overall view of the by the college goers and will present a comparison of the usage by the male and female undergraduates.